The effect of topical antibiotic or antibiotic-corticosteroid treatment on the ocular surface microbiota of healthy horses - M. G. Martin de Bustamante; C. E. Plummer; B. Caddey; D. E. Gomez (Frontiers in Microbiology)
IntroductionInformation regarding the impact of topical antibiotics with or without corticosteroids on the microbiota of the horses’ eyes is limited. This study aimed to describe the bacterial ocular surface microbiota in healthy horses and evaluate the effect of topical antibiotics or antibiotic-corticosteroid medication on the ocular surface microbiota.MethodsThis was a prospective, randomized, longitudinal, blinded study in which one eye of 12 horses was treated 3 times daily for 7 days with neomycin, polymyxin B and bacitracin ophthalmic ointment (n = 6) or neomycin, polymyxin B and dexamethasone ophthalmic ointment (n = 6). The contralateral eyes operated as untreated controls. The inferior conjunctival fornix of both eyes was sampled at baseline before antibiotic administration (day 0), on days 3, 7, 9, 14, and 30. The ocular surface microbiota was characterized by amplifying the V4 region of the 16S ribosomal RNA gene.ResultsAlpha- (richness and diversity) and beta-diversity (weighted and unweighted UniFrac distances) measurements of the ocular surface microbiota varied similarly after treatments starting on day 1, returning to baseline measurements by day 30. At baseline, the main phyla detected in the ocular microbiota was Proteobacteria, representing 75% relative abundance, followed by Firmicutes and Bacteroidetes. After treatments, Proteobacteria declined in all groups, and Firmicutes and Bacteroidete’s relative abundance increased, returning to baseline levels on day 30. The main genera detected on the ocular surface on day 0 were Suttonella, Nicoletella, Pasteurella, and members of the family Moraxellaceae. After treatment, the relative abundance of this bacteria declined in all groups, returning to baseline levels on day 30, although some alterations were still present.DiscussionHere we show that topical antibiotics administered with or without corticosteroids induce changes in the ocular surface of horses’ eyes, and the microbiota appears to return to baseline approximately three weeks after treatment discontinuation.